ANALISIS PENGARUH FAKTOR-FAKTOR BASE LENDING RATE TERHADAP RETURN ON EQUITY PADA KSP. MADANI NTB - Arsana, I Nengah; Irianto, Irianto; Kisnawati, Baiq (Jurnal Aplikasi Akuntansi, 2018)
This study entitled "Analysis of the Effects of Base Lending Rate Factors on Return On Equity On KSP. Madani NTB ". This study aims to measure the effect of partial and simultaneous variables factors Base Lending Rate (Cost of Laonable Fund, Overhead Cost, Risk Cost, Tax Rate) on Return On Equity on KSP. Madani NTB and analyze the variable Cost of Laonable Fund, Overhead Cost, Risk Cost, Tax Rate is the most dominant and significantly affect the Return On Equity on KSP. Madani NTB. The type of research used in this study is associative research. Data collection techniques conducted in this study are observation, interview and documentation. The type of data used is quantitative data. The procedure of data analysis using multiple regression model analysis. The results of this study indicate that the Cost of Laonable Fund, Overhead Cost, Risk Cost, Tax Rate is not entirely partially have a significant effect on Return on Equity on KSP.Madani NTB, caused by 1 (one) variable Tax Rate partially has no influence significant to the Return on Equity variable (Y), and all independent variables (Cost of Laonable Fund, Overhead Cost, Risk Cost, Tax Rate) simultaneously give a significant influence on the Return on Equity variable (Y). In addition, Risk Cost variable has the most dominant influence on Return on Equity in KSP.Madani NTB.